Pengaruh Perputaran Piutang dan Perputaran Modal Kerja Terhadap Net Profit Margin pada Perusahaan Makanan dan Minuman di BEI (2014-2018) - Wigianti Astutisari; Kristianingsih Kristianingsih; Ine Mayasari (Indonesian Journal of Economics and Management, 2020)
This research aims to find out the effect of Receivables Turnover and Working Capital Turnover on Net Profit Margin in Food and Beverage Sub Sector companies listed in IDX for the period 2014-2018. This study used purposive sampling techniques, so that sample data was obtained used by 6 Food and Beverage Sub Sektors companies registered in IDX period 2014-2018 with certain criteria. The type of data used in this study is secondary data in the form of the company's annual financial statements. The research method carried out is descriptive and quantitative research. This research was conducted by regression panel data processed using IBM SPSS Statistics 26 Software. The results showed that simultaneous turnover of receivables and turnover of working capital had a significant effect on Net Profit Margin. Partially, Receivables Turnover negatively and significantly affects Net Profit Margin and Working Capital Turnover negatively and significantly affects Net Profit Margin.